(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The research objective was to explore gender-based education policies were applied to elementary education in East Java Province. This research uses a qualitative approach. While the research method was a survey method. Data collection was carried out by making observations, interviews (including key informants), and documentation. The data required were primary and secondary data. Qualitative data to determine education policies from a gender perspective. Data analysis uses descriptive analysis using the Policy Outlook and Plan of Action (POP) approach model. The research conclusion was education policies in elementary education have a gender perspective. Unfortunately, the implementation of gender policies in elementary education was not evenly distributed among education policymakers in districts/cities in East Java Province due to the lack of gender understanding so there was often a gender gap in policymaking. The recommendation was gender policy implementation is promoted through to the provincial and district/city policymakers. Then, there is an understanding of the importance of gender, especially in elementary education.